THE FINANCIAL PLAN – A DEFINING ELEMENT IN DRAWING UP A BUSINESS PLAN - ANCA JARMILA GUŢĂ (Annals of the University of Petrosani: Economics)
This paper highlights the need for a financially well structured and based in the preparation of any business plan because it focuses on the financial section of the final SOCP any business that is making a profit. To highlight the importance of the financial plan presented in the paper there are the financial objectives of a business plan.